Language and the Rise of the Algorithm by Jeffrey M. Binder (review). - Petricek, Tomas (Technology & Culture, 2024)
"Language and the Rise of the Algorithm" by Jeffrey M. Binder explores the historical development of algorithms and their relationship to language. The book traces the emergence of symbolic notations and attempts to create universal languages, highlighting the changing relationship between symbolic systems and the messy world. It also discusses the evolution of algorithms in computer science, from the ALGOL programming language to predictive machine learning systems and large language models. The author emphasizes the importance of understanding the transformations of algorithms and symbolic notations in order to address issues such as algorithmic bias and the disconnect between computation and communication. The book is recommended for historians of technology and technologists designing new programming systems.